A Comparison of Transcriptional Patterns and Mycological Phenotypes following Infection of Fusarium graminearum by Four Mycoviruses - Lee, Kyung-Mi; Cho, Won Kyong; Yu, Jisuk; Son, Moonil; Choi, Hoseong; Min, Kyunghun; Lee, Yin-Won; Kim, Kook-Hyung (PloS one, 2014)
Many fungi-infecting viruses, which are termed mycoviruses, have been identified, and most do not cause any visible symptoms. Some mycoviruses, however, can attenuate the virulence of the infected fungi, a phenomenon referred to as hypovirulence. To study fungus responses to virus infection, we established a model system composed of Fusarium graminearum and four mycoviruses including FgV1 (Fusarium graminearum virus 1), FgV2, FgV3, and FgV4. FgV1 and FgV2 infections caused several phenotypic alterations in F. graminearum including abnormal colony morphology, defects in perithecium development, and reductions in growth rate, conidiation, and virulence. In contrast, FgV3 and FgV4 infections did not cause any phenotypic change. An RNA-Seq-based analysis of the host transcriptome identified four unique Fusarium transcriptomes, one for each of the four mycoviruses. Unexpectedly, the fungal host transcriptome was more affected by FgV1 and FgV4 infections than by FgV2 and FgV3 infections. Gene ontology (GO) enrichment analysis revealed that FgV1 and FgV3 infections resulted in down-regulation of host genes required for cellular transport systems. FgV4 infection reduced the expression of genes involved in RNA processing and ribosome assembly. We also found 12 genes that were differentially expressed in response to all four mycovirus infections. Unfortunately, functions of most of these genes are still unknown. Taken together, our analysis provides further detailed insights into the interactions between mycoviruses and F. graminearum.